Cold-hearted or cool-headed: physical coldness promotes utilitarian moral judgment - Nakamura, Hiroko; Ito, Yuichi; Honma, Yoshiko; Mori, Takuya; Kawaguchi, Jun (Frontiers in Psychology, 2014)
In the current study, we examine the effect of physical coldness on personal moral dilemma judgment. Previous studies have indicated that utilitarian moral judgment—sacrificing a few people to achieve the greater good for others—was facilitated when: (1) participants suppressed an initial emotional response and deliberately thought about the utility of outcomes; (2) participants had a high-level construal mindset and focused on abstract goals (e.g., save many); or (3) there was a decreasing emotional response to sacrificing a few. In two experiments, we exposed participants to extreme cold or typical room temperature and then asked them to make personal moral dilemma judgments. The results of Experiment 1 indicated that coldness prompted utilitarian judgment, but the effect of coldness was independent from deliberate thought or abstract high-level construal mindset. As Experiment 2 revealed, coldness facilitated utilitarian judgment via reduced empathic feelings. Therefore, physical coldness did not affect the “cool-headed” deliberate process or the abstract high-level construal mindset. Rather, coldness biased people toward being “cold-hearted,” reduced empathetic concern about a sacrificed victim, and facilitated utilitarian moral judgments.